Applying art therapy in improving resilience in child victims of domestic violence - Basyiroh, Arifah Nur; Yuniarti, Kwartarini Wahyu (Universitas Muhammadiyah Surakarta, 2020)
Domestic violence experienced by children make them more prone to emotional, behavior, adaptation and mental health problems. Some researches show that children with high resiliency are able to develop a positive attitude, perspective and adaptability despite a history of violence. The purpose of this study was to determine the effect of CBT Art Therapy intervention to increase the resiliency of children expose to domestic violence. The method used in this research is single case single-subject experiment ABA design. Resilience measurement instruments used in this research are Quotient Test (RQT) and resilience behavior observation sheet. Data were analyzed through visual analysis and descriptive data analysis. The results showed an increasing score in RQT (27 points) as well as the intensity of resilience behavior and positive changes in the use of color, quality and theme of the artwork. Keywords: art therapy, resilience, child victims of domestic violence, single case single-subject experiment